ASEPTIK NEKROSIS OF FEMORAL HEAD RADIACION DIAGNOSTICS (Conferencea, 2023)
Aseptic necrosis of the femoral head is a medical problem of social importance. The reason for this is that this pathology mainly affects people of working age. If the diagnosis is not detected in time or is insufficient, it leads to disability and a decrease in the quality of life.